Strategy scenario selection in the competition of mobile ecosystems - Hyun Joo Lee; Jin Ki Kim (International Telecommunications Society (ITS), 2013)
Competition in the mobile market is centered on platforms, or operating systems, for smartphones. The current competition and market structure of the global mobile market has shifted to a competition among ecosystems that utilize the same mobile operating systems of the platform operators. This paper aims to answer those questions. The direction of competition in the smartphone industry is traced. This study tries to list the selectable strategy options for each major ecosystem. Then the strategy options for each ecosystem are tested in terms of their desirability from the viewpoint of industry experts. Finally, this study tries to put the puzzle together based on the most desirable strategy options for each ecosystem.
Keywords: 330